Turbulence and the employment experience of older workers - Etienne Lalé (Quantitative Economics, 2018)
This paper provides new interpretations of the effects of rising economic turbulence-an increase in the rate of skill depreciation upon job loss-and its interaction with labor market institutions. We have three main results, based on a life-cycle model with labor market frictions and labor force participation decisions. First, rising economic turbulence during the 1970s and 1980s accounts for the decline in employment among older workers in the United States. Second, the interaction between turbulence and institutions explains most of the reduction in labor force participation among older workers in Europe over this period, but ultimately explains little of the rise in unemployment. Third, only a small share of the increase in unemployment can be attributed to the early retirement policies that were implemented in Europe from the 1970s up until the early 1990s. Our analysis indicates that incorporating an operative labor supply choice can pose serious challenges to theories aiming to explain the European unemployment problem.
Keywords: E24; J21; J64; 330; Job search; job loss; turbulence European unemployment; labor force participation